2018
DOI: 10.1016/j.bbrc.2018.08.126
|View full text |Cite
|
Sign up to set email alerts
|

CELF1 contributes to aberrant alternative splicing patterns in the type 1 diabetic heart

Abstract: Dysregulated alternative splicing (AS) that contributes to diabetes pathogenesis has been identified, but little is known about the RNA binding proteins (RBPs) involved. We have previously found that the RBP CELF1 is upregulated in the diabetic heart; however, it is unclear if CELF1 contributes to diabetes-induced AS changes. Utilizing genome wide approaches, we identified extensive changes in AS patterns in Type 1 diabetic (T1D) mouse hearts. We discovered that many aberrantly spliced genes in T1D hearts have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…To identify the DAS events, we performed DAS analysis [57][58][59][60][61] . Briefly, the raw RNA-Seq reads first were aligned to mouse genome (mm9) using STAR 62 with default settings, and those uniquely mapped reads were retained to calculate the counts of the reads for each exon and each exon-exon junction annotated in the UCSC knownGene (mm9) table 63 using the Python package HTSeq 64 .…”
Section: Das Analysis Using Rna-seq Datamentioning
confidence: 99%
“…To identify the DAS events, we performed DAS analysis [57][58][59][60][61] . Briefly, the raw RNA-Seq reads first were aligned to mouse genome (mm9) using STAR 62 with default settings, and those uniquely mapped reads were retained to calculate the counts of the reads for each exon and each exon-exon junction annotated in the UCSC knownGene (mm9) table 63 using the Python package HTSeq 64 .…”
Section: Das Analysis Using Rna-seq Datamentioning
confidence: 99%
“…To determine how PTBP1 splicing is modulated in T1D mouse hearts and during mouse heart development, we tested whether CELF1 and RBFOX2 are involved. We have previously shown that both CELF1 and RBFOX2 protein levels are modulated in the diabetic heart [19][20][21]. These proteins are involved in developmental regulation of AS in the heart [16,26,27].…”
Section: Regulation Of Diabetes-induced and Developmentally Regulatedmentioning
confidence: 97%
“…Streptozotocin (STZ) induced T1D and non-obese diabetic (NOD) mice were used for our experiments as described previously [19][20][21]. Animal experiments approved by the University of Texas Medical Branch Institutional Animal Care and Use Committee (Protocol # 1101001) were conducted in compliance with the NIH Guidelines.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the DAS events, we performed DAS analysis 57,58,59,60,61 . Briefly, the raw RNA-Seq reads first were aligned to mouse genome (mm9) using STAR 62 with default settings, and those uniquely mapped reads were retained to calculate the counts of the reads for each exon and each exon-exon junction annotated in the UCSC knownGene (mm9) table 63 using the Python package HTSeq 64 .…”
Section: Das Analysis Using Rna-seq Datamentioning
confidence: 99%